Akitivitas Fisik Dan Pola Makan Dengan Kejadian Hipertensi - Lilipory, Mevi (Lembaga Penerbitan Fakultas Kesehatan Universitas Kristen Indonesia Maluku, 2023)
The incidence of hypertension increases with age. Elderly people tend to experiencehypertension due to atherosclerosis and stiffness, decreased ability of cardiaccontractility, reduced elasticity of blood vessels, and lack of effectiveness of peripheralblood vessels for oxygenation. Adequate physical activity can help strengthen the heart.Food intake with high fat and sodium content can affect the high and low blood pressurein the body, causing hypertension. The purpose of this study was to determine therelationship of physical activity and eating patterns with the incidence of hypertension inthe elderly. This Systematic Review aims to determine the relationship of physical activityand eating patterns with the incidence of hypertension in the elderly. The method useduses Review articles and nursing journals. The results of various articles and journalsconducted show that there is a relationship between physical activity and eating patternswith the incidence of hypertension in the elderly. Lack of physical activity makes thebody's organs and blood and oxygen supply choked up thereby increasing bloodpressure. Unhealthy eating patterns, namely the habit of consuming food without regardto the type and ingredients, it can lead to obesity which results in narrowing of bloodvessels so that the heart muscle must be harder to pump blood so that leads to highblood pressure. Thus it can be concluded that there is a significant relationship betweenphysical activity and diet with the incidence of hypertension in the elderly. So it issuggested to be useful information for the community in maintaining health status byalways doing physical activities such as regular exercise and maintaining a healthy dietso that it can reduce the incidence of hypertension. Keywords: Physical Activity, Diet, Hypertension, Elderly